Accuracy of Impression Techniques for an Implant-Supported Prosthesis - Del'Acqua, Marcelo Antonialli; Chavez, Alejandro Munoz [UNESP]; Compagnoni, Marco Antonio [UNESP]; Mollo Junior, Francisco de Assis [UNESP] (Quintessence Publishing Co Inc, 2010)
Purpose: This in vitro study compared the dimensional accuracy of a stone index and of two impression techniques (squared impression copings and modified squared impression copings) for implant-supported prostheses. Materials and Methods: A master cast with four parallel implant-abutment analogs and a passive framework were fabricated. Vinyl polysiloxane impression material was used for all impressions with a metal stock tray. Three groups of impressions were tested (n = 5): index (1), squared (S), and modified squared (MS). The measurement method employed was just one titanium screw tightened to the framework. The measurements (60 gap values) were analyzed using software that received the images from a video camera coupled to a stereomicroscope at x 100 magnification. The results were evaluated statistically (analysis of variance, Holm-Sidak method, alpha = .05). Results: The mean abutment/framework interface gaps were: master cast = 31.63 mu m; group I = 45.25 mu m; group S = 96.14 mu m; group MS = 51.20 mu m. No significant difference was detected among the index and modified squared techniques (P = .05). Conclusion: Under the limitations of this study, the techniques modified squared and index generated more accurate casts than the squared technique. INT J ORAL MAXILLOFAC IMPLANTS 2010;25:715-721
Keywords: dental implants; dental impression technique; dental models